The Role of History Learning in Instilling Religious Character and Nationalism in MAN Temanggung - Winarsih, Idha; Utomo, Cahyo Budi; Ahmad, Tsabit Azinar (Universitas Negeri Semarang, 2020)
This research aims to describe the religious attitude and nationalism raised by the students of MAN Temanggung, explain the role of learning history in the cultivation of the value of spiritual character and nationalism in MAN Temanggung, and know the constraints faced by teachers in planting the value of religious character and nationalism in MAN Temanggung. The method in this research is qualitative. Result of study: 1. the attitude of religious and student nationalism at MAN Temanggung can be classified as good. This can be seen from the programs implemented by the school as the school’s rules, as long as it becomes a student’s habit; 2. The role of history learning as the implementation of religious values can be seen when the teacher serves the material about Islamic Civilization in Indonesia. Moreover, the role of history teaching in implementing nationalism can be seen when teachers deliver material about the Proclamation; 3. The teachers' obstacles include the planning, implementation, and evaluation process. The barriers in the planning process include a lack of supporting books that can increase historical material references. The obstacles to the implementation are the lack of time and the differences in students' character. The barrier in the evaluation is that the teachers cannot understand the character of each student.